STUDI PERBANDINGAN KADAR FOSFOR DARI FOSFOLIPID MEMBRAN ERITROSIT NORMAL DAN ERITROSIT PENDERITA HIPERTENSI - Maniur Arianto Siahaan (Jurnal Analis Laboratorium Medik, 2020)
Research was done to determine the phospholipid types and the phosphorus concentration in the total phospholipids extracted from the erythrocytes from patients with normal blood pressure and patients with hypertention. Bloods samples from normal bloods pressure patients and hypertention patients were separated by centrifuge to obtain erythrocytes which were then extracted to obtain lipids. The phospholipids types were determined by thin layer hromatography and the phosphorous concentration were measure by spectrophotometry. Both blood samples contained the phospholipid types, however the phosphorous concentration of total phospholipid was highes in erythrocytes of the hypertention patient than the normal blood pressure patien, or an average of 3,2376 mg/ml from erythrocytes of hypertention patient and 1,6199 mg/ml from normal blood pressure patien